Demands placed upon individual techniques fulfillment in volleyball - Tinyukov, A. B.; Timoshina, I. N.; Kostyunina, L. I. (The Russian Journal of Physical Education and Sport, 2017)
Volleyball players` technique and tactics are characterized by constant search for the ways of individual peculiarities realization of the leading techniques fulfillment with the use of innovative approaches, which provide new forms of movements appearance on the basis of earlier mastered movements. Difficult technical-tactical technique realization in volleyball is conditioned by the process of an adequate perception and quick monitoring of the situation during the game on the basis of extrapolation and further duration of spots combat. Materials. Theoretical and methodological substantiation ofthe need for modern system of training among female volleyball players modernization, the methodology creation of qualified female volleyball players training in accordance with new demands, tendencies of modern volleyball development. Research methods: scientific and scientific-methodical literature analysis and systematization, testing, pedagogical experiment, statistical data handling. Results. The article determined the demands placed upon sports training organization among volleyball players at a modern stage, conditioned by volleyball development tendencies. The methodology of individual skills of techniques formation is created, which are directed at easiness of motor acts and sense of proportion generation. Motional tasks were included into the content of preparatory, main and final parts of the training, into games and competitions, where the conditions of their fulfillment were considerably complicated. Conclusion. The results of the held pedagogical experiment prove the effectiveness of the offered methodology of the training process organization. Demands, placed upon sports improvement of female volleyball players, condition the search for nonstandard solutions, which provide creative participation of female athletes in the quality of the training lessons improvement. Individual technique formation of the leading techniques fulfillment, such as the sense of easiness in difficult motional actions and sense of proportion, while choosing an optimal rhythm and tempo of motional actions, provided female volleyball players` kinesiological potential successful realization, the skills of spatio-power and spatio-temporal orientation in playing activity formation among female volleyball players, which helped to improve greatly qualified female athletes` indices of general physical and technical readiness.